2021
DOI: 10.7759/cureus.12911
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Vitamin D and Immunoglobulin E Levels With Severity of Allergic Rhinitis

Abstract: Objective The aim of this study was to determine the association of serum vitamin D and immunoglobulin E (IgE) levels with the severity of allergic rhinitis (AR). Methods This case-control study was conducted at Mayo Hospital, Lahore, from June to September 2020 after obtaining ethical approval. Patients of AR were included and divided with the help of allergic rhinitis and its impact on asthma (ARIA) classification, into group A (cases), patients presenting with moderate to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Elevated total serum IgE was a common finding in allergic conditions, which can help clinicians to verify the diagnosis of bronchial asthma or allergic rhinitis. A higher total serum IgE level is linked with a greater burden of disease exemplified in a study by Nukhbat et al, who found that serum IgE levels were higher in moderate to severe AR compared to the milder form [24]. The majority of our patients had an elevated total serum IgE and it is associated with a significantly higher medication adherence.…”
Section: Main Findingssupporting
confidence: 56%
“…Elevated total serum IgE was a common finding in allergic conditions, which can help clinicians to verify the diagnosis of bronchial asthma or allergic rhinitis. A higher total serum IgE level is linked with a greater burden of disease exemplified in a study by Nukhbat et al, who found that serum IgE levels were higher in moderate to severe AR compared to the milder form [24]. The majority of our patients had an elevated total serum IgE and it is associated with a significantly higher medication adherence.…”
Section: Main Findingssupporting
confidence: 56%
“…Allergic rhinitis is one of the most common pediatric diseases with high incidence worldwide [17][18][19][20]. In recent years, the incidence of allergic rhinitis and some respiratory diseases has increased significantly with the aggravation of air pollution and environmental deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations have been carried out in different populations to explore the possible link between vitamin D and AR; however, the results remained contradictory. Although vitamin D deficiency has been related to susceptibility to AR in a wide range of populations [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] ], there are reports highlighting the absence of a link between vitamin D and allergic rhinitis [ 20 , 21 ]. Furthermore, another study in Pakistanis [ 10 ] found that 10% of AR had adequate vitamin D levels compared to 26% of healthy controls, but the difference was not statistically significant.…”
Section: Introductionmentioning
confidence: 99%